(untitled) (Malaysian Journal of Learning and Instruction, 2023)
Purpose - Empathy portrays a pivotal role in moulding an individual into an affectionate human being. Numerous studies examine empathy in multicultural settings; however, it is still clouded with scarcity, especially in the Asian context. This study aims to explore the approaches two teachers had undertaken to develop empathy among multicultural students in their Moral Education lessons in Malaysian schools. Methodology - This study adopted a case study approach to investigate empathy development among multicultural 16-year-old students. The participants were two teachers who taught Moral Education (ME) in their respective schools. Data were collected for eight months through observations, interviews, teachers’ journals, and documents until saturated. Analysis was done using NVivo 8 software. Findings - Five categories were formed from the emergence of a single theme, ‘instilling empathy’ that revealed the representation of the approaches to be homogeneous between the two teachers. The categories were role-taking, watching movies, sharing stories, social activity, and discussion. The findings revealed the existence of limited strategies employed by the teachers in instilling empathy among the students, illuminating cognitive empathy over affective empathy. Significance - This study implied that teachers need more training on various methods to instil empathy, especially among students from multicultural backgrounds. This could lead to empathy training programmes that is relatively new in Malaysian schools that could benefit the young to enable them to work effectively in multicultural settings reflecting the diversity of this country.